GUS MARCH-PHILLIPS’ TRANSFORMATIONAL LEADERSHIP IN CULTIVATING SUPPORTIVE ENVIRONMENT IN THE MINISTRY OF UNGENTLEMANLY WARFARE FILM - Dewi Syifanaya Firdausy Nurdin; Qurrota A'yunin; Romadhona Resa Ayu Sari; Bagus Pratama Wijayanto; Rommel Utungga Pasopati; Cahyaningsih Pujimahanani; Dimas Eko Saputro (LPPM Universitas PGRI Adi Buana, 2025)
This study examines the reason behind transformational leadership is portrayed, namely the idea of cultivating a supportive environment, as exemplified by Gus March-Phillips in Guy Ritchie's film The Ministry of Ungentlemanly Warfare. The movie, which is set during World War II, emphasizes how Gus's leadership promotes friendship, and fostered a more inclusive and supportive work environment where team members feel valued and engaged. The research demonstrates Gus's capacity to build strong trust-based relationships with his followers, and allowing members to express their concerns freely through a qualitative examination of significant conversations and situations. The results show behind Gus’ cultivating a supportive environment and regard for motivated to contribute, which are hallmarks of transformational leadership, can improve team cohesiveness and personal development.